Ответы и объяснения

2012-04-13T12:06:42+00:00

4. А) sin^2 a/(ctg^2 a-cos^2 a) = sin^2 a/(sin^2 a/((cos^2 a  - cos^2 a*sin^2a)/sin^2a)=  sin^4 a/(cos^2a - cos^2 a*sin^2a)=sin^4/cos^2a(1-sin^2a)=sin^4 a/cos^4a=tg^4a

Б) 1/cos x -cos x = cos (x-пи/2)*ctg(3пи/2-x);

1/cos x -cos x = sinx*tgx;

1-cos^2x/cosx = sin^2x/cosx

sin^2x/cosx= sin^2x/cosx

5) tg a*ctg a=1
tg a*ctg a =  (sin^4a-cos^4a)*2/(sin^2a - cos^2a)=2(sin^2a-cos^2a)(sin^2a+Cos^2a)/(sin^2a-Cos^2a)=2*(sin^2a+Cos^2a)=следует не существует